Analysis and Design of Web Server Security Systems From XSS and CSRF Defacement - Muhd Iqbal; Umam Farizan; Rasudin Abubakar (Proceedings of International Conference on Multidisciplinary Engineering (ICOMDEN), 2018)
This study aims to identify the signs of defacement in detail and design web-server security system Automatic Interactive Reactive Intuition Detection System (AIRIDS) method to maintain the confidentiality of data from irresponsible parties and improve the security and filtering of data traffic on the web-server. The method used in this research is network and webserver analysis method which is done by analyzing existing web-server and website that has been active using Acunetix wvs 10.5 software, method of attacking web-server system done with scenario I (web attack local defacement) and scenario II (outside defacement). The parameters observed are the web server security topology, the designed system, the prevention of XSS and CSRF as well as the installation of AIRIDS. The results show that the website and web-server prior to installation of AIRIDS can be attacked by defacing techniques and high-level web server vulnerabilities (high = 3), but after installation of web-server security system, website and web-server cannot be attacked with defacing technique and not get back gap that status high (high = 0). It can be concluded that the installation of web-server security system AIRIDS method can prevent and minimize the level of vulnerability of attacks on websites and web-server, but it also can prevent the leakage of confidential information.